Escape From Anxiety Of Dorian Gray In Oscar Wilde's The Picture Ofdorian Gray: A Psychoanalytic Approach - Rahayu, Sri (2004)
The major problem of this research is how the major character escapes from the anxiety, resulted from unhandled problems he encounters. The objective of the study is to identify the relation between the causes of anxiety and the ways to escape from anxiety faced by the major character, using the structural and the psychoanalytic analysis. In so doing, the object of the study is Oscar Wilde's The Picture of Dorian Gray, giving focus on one of the major characters, namely Dorian Gray. In analyzing The Picture of Dorian Gray, the writer uses a qualitative method. The data sources are primary and secondary data source. The primary data source is the novel of The Picture of Dorian Gray itself and the secondary data source are other sources related to the analysis such as the author's biography, books of literary theory and psychological books, specially psychoanalysis theory of Sigmund Freud. The method of data collection is library research. The technique of data analysis are descriptive analysis and hermeneutic. The outcome of the study shows that the problem faced by the major character causes the conflict of his mental condition. It brings him in anxiety which influences him to do some ways to escape from his anxiety. Actually, these ways are not the effective ways to overcome the problem.